The Effects of Changes in the Unemployment Compensation System on the Adoption of IT by Older Workers - Alexandra Spitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Two main hypotheses can be found in literature on why elderly workers have a lower probability of using information technology than their younger peers: lower learning capabilities and reduced incentives to invest in human capital. I use law changes in the unemployment compensation system enacted in Germany during the 1980s and 1990s to demonstrate that ?incentives? are more important than ?capabilities? in determining variation in IT usage. Elderly workers only fell behind the IT usage rates of their younger peers during the 1980s and 1990s, when unemployment benefits got increasingly generous, thereby reducing their incentives to invest in human capital.
Keywords: J24; J14; 330; differences-in-differences; computer adoption by older workers; changes in unemployment compensation system; Bildungsinvestition; Weiterbildung; Computergestütztes Verfahren; Ökonomischer Anreiz; Arbeitslosigkeit; Arbeitslosenversicherung; Schätzung; Deutschland